2015
DOI: 10.1038/modpathol.2014.86
|View full text |Cite
|
Sign up to set email alerts
|

Succinate dehydrogenase-deficient renal cell carcinoma: detailed characterization of 11 tumors defining a unique subtype of renal cell carcinoma

Abstract: Patients with germline mutation of succinate dehydrogenase (SDH) subunit genes are prone to develop paraganglioma, gastrointestinal stromal tumor, and rarely renal cell carcinoma (RCC). However, SDH-deficient RCC is not yet widely recognized. We identified such tumors by distinctive morphology and confirmed absence of immunohistochemical staining for SDHB. Immunohistochemical features were evaluated using a panel of antibodies to renal tumor antigens. Targeted next-generation sequencing was performed on DNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
215
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(224 citation statements)
references
References 37 publications
4
215
0
5
Order By: Relevance
“…43 SDH-deficient RCCs display a slight male predisposition, present as bilateral tumors in 25% of cases, and have stereotypical morphologic features, that is, solid or focally cystic growth, uniform cytology with eosinophilic flocculent cytoplasm, intracytoplasmic vacuolations and inclusions, round to oval low-grade nuclei, and SDHB immunonegativity. 44,45 SDHA-negative IHC was reported once, but no mutational screening of SDHA was performed. 44 Despite the fact that SDH-deficient RCC is capable of progression, metastatic disease is rare in the absence of high-grade nuclear atypia or coagulative necrosis.…”
Section: Genotype-phenotype Correlation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…43 SDH-deficient RCCs display a slight male predisposition, present as bilateral tumors in 25% of cases, and have stereotypical morphologic features, that is, solid or focally cystic growth, uniform cytology with eosinophilic flocculent cytoplasm, intracytoplasmic vacuolations and inclusions, round to oval low-grade nuclei, and SDHB immunonegativity. 44,45 SDHA-negative IHC was reported once, but no mutational screening of SDHA was performed. 44 Despite the fact that SDH-deficient RCC is capable of progression, metastatic disease is rare in the absence of high-grade nuclear atypia or coagulative necrosis.…”
Section: Genotype-phenotype Correlation Analysismentioning
confidence: 99%
“…44,45 SDHA-negative IHC was reported once, but no mutational screening of SDHA was performed. 44 Despite the fact that SDH-deficient RCC is capable of progression, metastatic disease is rare in the absence of high-grade nuclear atypia or coagulative necrosis. 44,45 Finally, SDH-deficient PAs seem likely to be prolactin-secreting (and/or prolactin-immunopositive) and, to a lesser extent, growth hormone-secreting macroadenomas.…”
Section: Genotype-phenotype Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these changes are thought to drive tumorigenesis in the multiple organ systems that demonstrate increased incidence of neoplasia in individuals harboring germline SDHx mutations, which include paragangliomas/pheochromocytomas, GISTs and, among a subset, a histologically distinctive type of renal cell carcinoma (Gill et al 2014, Williamson et al 2015. Importantly, with regard to GISTs, SDH-deficient GISTs can be due to either genetic (SDHA, B, C or D mutations) or epigenetic (SDHC promoter methylation) changes.…”
Section: Sdh-deficient Gists (Sdha B C D Mutations Sdhc Epimutants)mentioning
confidence: 99%
“…Most participants (59%) reported that they perform succinate dehydrogenase (SDH) immunohistochemical staining only with unusual or borderline morphology (59%), or when morphology is highly suggestive of SDHdeficient renal cell carcinoma (29%). [13,14] None of the participants reported screening oncocytic tumors routinely for SDH status.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%